Titanium-catalyzed hydrohydrazination of carbodiimides - Schweizer, Peter Dominik; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2013)
Hydrazinediido complexes of the type [Cp*Ti(NxylN)(NNR2)(L)] (R = Ph, Me; Ar, fluorene, L = tBuNH2, Py; 3a–e) have been synthesized and used as catalysts for the hydrohydrazination of a series of carbodiimides, yielding aminoguanidines or fluoreneiminoguanidines. The highest yields were obtained for diarylhydrazines and fluorenone hydrazone at temperatures between 80 and 105 °C. Stoichiometric reactions of hydrazinediido complexes with iPrNCNiPr led to an equilibrium with the resulting [2 + 2] cycloadducts 4a–f, which were characterized by 1H, 13C, and 15N NMR spectroscopy as well as X-ray diffraction. The proposed mechanism, which is closely related to that previously established for the hydrohydrazination of alkynes and allenes, was found to be consistent with the results of a kinetic study. The dynamic structures of aminoguanidines and fluoreneiminoguanidines were characterized by NMR spectroscopy, and the minimum configurations were found to be stabilized by intramolecular hydrogen bonding.